Modernization of Islamic Education: Efforts to Preserve Islamic Values amid the Development of Digital Technology - Variza Wamer Erliana; Syamsul Aripin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of digital technology has brought significant changes to the education system, including Islamic education. Modernization of Islamic education has become a necessity to adapt the learning process to current developments, but this can also pose challenges in maintaining Islamic values. This article aims to examine the concept of modernizing Islamic education, the challenges in modernizing Islamic education, and efforts to maintain Islamic values. The method used in writing this article is a qualitative approach with a literature review, through a review of various journal articles relevant to the topic. The results of the study indicate that modernization of Islamic education can be aligned with Islamic values if digital technology is used wisely and integrated into the formation of good morals and ethics in students. Therefore, the active role of teachers and educational institutions is needed to optimize digital technology as a learning tool without neglecting Islamic values.